20. Yüzyılın İlk Yarısında Türkiye’nin Sosyal Haritasına Bir Bakış - Hikmet ÖKSÜZ; Yüksel KÜÇÜKER (Gazi Akademik Bakış)
Historically, the most significant changes in the demographical structure of Anatolia have occurred in the last 150 years. In the last two centuries of the Ottoman Empire, the territories began to shrink as a result of the weakening of the Empire, losing wars and thus, losing significant portions of lands. The region that was affected most from this territorial shrinking process was Anatolia, which was considered as a safe haven at the nucleus of the Ottoman Empire. It is a commonly held view that the Ottoman-Russian War of 1877-1878 (the War of ‘93) was a critical point for the demographic structure of Anatolia. As a result of the disastrous defeat suffered at the hands of the Tsarist Russia the Muslim populations of the Balkans immigrated en masse to the Anatolian territories. This immigration wave left lasting effects on the demographic structure of the Ottoman Empire while at the same time creating the opportunity for the Balkan nations to constitute their nation-states. The independence movements in the Balkans were followed by the political changes in the Caucasian region and the Muslims of Crimea and Caucasia began to flood into Anatolia in large numbers beginning in the 1860s. The new “national” Turkish state, founded after the War of National Struggle in the first quarter of the 20th century, has been well established on a sociological basis in terms of nation-building with the integration of the Muslim refugees from the Balkans and the Caucasus with the native Muslim population of Anatolia. This nation-building process of modern Turkey during the first half of the 20th century was closely examined by the American officials who compiled a social and demographic map of Turkey.